Loperamide increases mouse gut transit time in a dose-dependent manner with treatment duration-dependent effects on distinct gut microbial taxa - Anna Pii Hjørne; Martin Steen Mortensen; Tine Rask Licht; Martin Frederik Laursen (Gut Microbiome)
Intestinal transit time has been recognized as an important factor in shaping the gut microbiota, although causality remains to be firmly demonstrated. The aim of this study was to evaluate the effect of different loperamide doses on the mouse intestinal transit time and to investigate the effects of increasing transit time on the gut microbial community. Loperamide significantly increased the transit time in a dose-dependent manner. Additionally, we observed a significant difference between the control group and the loperamide-treated groups in the abundance of the bacterial families Bacteroidaceae, Erysipelotrichaceae, Porphyromonadaceae, and Akkermansiaceae after 7 days of loperamide treatment, with the bacterial families responding to the increased transit time at different rates. Fermentation of faeces obtained from the same mice, with or without loperamide, demonstrated that the observed effects on gut microbiota in vivo were not a result of direct interactions between loperamide and the gut microbiota but rather a consequence of loperamide-induced increased intestinal transit time. In the cecum of the mice, we found higher levels of propionate in the high-dose group compared to the control and low-dose groups. Collectively, our findings establish that an altered transit time is causal to changes in the composition and activity of the microbiome.